1998
DOI: 10.1111/j.1151-2916.1998.tb02676.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Silicon Nitride Grown from a Liquid Phase

Abstract: To explain the recent experimental observation of liquidgrown silicon nitride (Si 3 N 4 ) crystals with a concave depression in the center of the (0001) end face, we propose a new growth mechanism and develop an analytical solution for the steady state. The model allows for atoms that diffuse via the liquid to the side surface but demands that the majority of these atoms be transported to the end caps to feed axial growth. The analysis shows that, for a large radius crystal, the redistribution of atoms by surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the second article (Part II), we describe the crystal population dynamics to determine the growth velocity and to make a comparison with the theoretical predictions of crystal growth and coarsening based on a recent theory. 11 A further examination and modeling of the shape transition at the ends of a rod-shaped crystal 12 are reported elsewhere using the dimensional and velocity data obtained here.…”
Section: Introductionmentioning
confidence: 83%
“…In the second article (Part II), we describe the crystal population dynamics to determine the growth velocity and to make a comparison with the theoretical predictions of crystal growth and coarsening based on a recent theory. 11 A further examination and modeling of the shape transition at the ends of a rod-shaped crystal 12 are reported elsewhere using the dimensional and velocity data obtained here.…”
Section: Introductionmentioning
confidence: 83%
“…(1) In their comment on our paper, 1 Kitayama et al 2 suggested that the weighted mean curvature method should have been used to obtain surface chemical potential. Their results are correct, but only for crystals that have a flat end.…”
mentioning
confidence: 99%
“…They are certainly not useful for treating surface morphology that has undulations. 1 (2) To allow a more general discussion not restricted to grains with flat ends, we have derived the surface potential for a rod-shaped crystal having spherical end caps and a circular cross section. The derivation, which is consistent with the weight mean curvature concept, will be published elsewhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I N THEIR recent paper, Wang et al 1 proposed a new growth mechanism, and developed an analytical solution for the steady state to explain their experimental observation of liquid-grown silicon nitride (Si 3 N 4 ) crystals with a concave depression in the center of the (001) end face. The key to their analysis is that the chemical potential at the center is lower than the edge as evidenced by the negative curvature at the center.…”
mentioning
confidence: 99%